Suspending the promotion of the public employee Acritical analytical study in light of the civil service legislations in force in the Kurdistan Region of Iraq - محمد محمد سليم محمد أمين سليم (Journal of Legal Sciences, 2021)
The research came to study one of the most important legal rights of the public employee in the Kurdistan region, which is stated at "The Salaries and State Employees Law No. 22 of 2008" and other relevant legislation in force of Kurdistan Region, which is the right to be promoted as one of the financial and moral rights of the public employee, where he Highlight the decision to suspend the legal system for promotion by a decision issued by the executive authority in the region, which is Administrative decision No. (11) for the year 2016 and was issued by the Ministry of Finance and Economy in the region. The study concluded the illegality of the aforementioned decision, especially in terms of the defect of gross lack of jurisdiction that descends the decision to the degree of absence, as it included a clear and explicit attack on the legislative authority by the executive authority, as well as the result of the decision and still has negative effects on the public job and the performance of the public employee in the region The study suggested that the aforementioned decision should be canceled, that employees who were affected by that decision should be compensated, and that a unified law for the civil service in the region should be enacted that includes all civil service systems, including promotion, in a manner that guarantees all the rights of the region’s employees and a measure of job justice that all employees in the region seek.